The Effect of Agung Semeru Banana Peel Extract as Biostimulation of Indegenous Bacteria in Reducing Ammonia - Mohammad Rizky Ramadhan; Dwi Nur Rikhma Sari; Mohamad Syaifudin Aswan; Septarini Dian Anitasari (Biota, 2023)
Ammonia is one of the hazardous compounds, which is contained in the liquid waste of rubber factories. Ammonia waste can cause various kinds of pollution, one of which is water pollution. The purpose of this study was to determine the effectiveness of the agung semeru banana peel extract as additional nutrition for indigenous bacteria in reducing ammonia levels. This research was conducted in the Biology laboratory, PGRI Argopuro University, Jember. This study uses a simple bioreactor as a tool to determine the decrease in ammonia levels in various treatments. The treatment in this study was using different concentrations of different banana peel extracts (0%, 5%, 10%). Based on the analysis of research data, it showed that Agung Semeru banana peel extract as an additional nutrient for indigenous bacteria was effective in reducing ammonia levels. At 10% banana peel extract concentration, the lowest ammonia level was in the range of 0.25-0.5 compared to the control concentration, namely 2. The higher the concentration of banana peel extract given, the lower the ammonia content in rubber waste.